Urban retail management: Lille and Roubaix (Ciudades, 2018)
The polycentric Lille metropolitan area, in the northern part of France, is easily connected with important international cities, such as Paris, London and Brussels. In this metropolitan area interesting experiences have been run of centralized retail management, partly referred to the Belgian and the English experiences of Town Centre Management. The activities of centralized management, both of town centres and, specifically, of urban retail, have been implemented in the two main centres of the area - Lille and Roubaix - following different orientations. Roubaix’s local commercial system has been heavily affected both by the economical crisis related to the decline of industrial activities and by the development of large suburban retail implantations. The activity of the association for the revitalization of central retail has been mainly supported by public policies. In Lille the stronger local economical system, reinforced by the programs of modernization of the international high-speed railways and the connected urban projects (Euralille) has received an important impulse for its revitalization by private enterprises.
Keywords: Lille; Roubaix; retail planning and town centre management